The Effect of Trust, Tax Rates and Tax Awareness on the Compliance Level of MSME Taxpayers at KPP Pratama Batam Selatan - Taufan Maulamin; Joni (IJESS International Journal of Education and Social Science, 2021)
Since the discovery of the Corona virus in Indonesia, economic growth has contracted at 2.97% and 5.32% respectively in the first and second quarters of 2020. Indonesia has just emerged from recession starting in the 3rd quarter with economic growth of 5.05%. But overall, in 2020 the Indonesian economy fell 2.07% compared to the previous years which was stable at 5% (BPS, 2021). This decline in economic growth has had a significant economic impact. In 2020 and 2021, several times the government implemented Large-Scale Social Restrictions (PPKM) so that many businesses, both small and large scale, felt the impact, and even closed their businesses. This systematic impact also affects state revenues from the tax sector. Targeted tax revenues according to Presidential Decree No. 72 of 2020, The Directorate General of Taxes (DGT) of the Ministry of Finance of Rp. 1,198.82 trillion has only realized Rp. 1,069.98 trillion or 89.25%. State revenues from the tax sector long before the outbreak of the Covid-19 pandemic actually tended to be low. One sector that contributes to state tax revenues that should be large but far from the target is the Micro, Small and Medium Enterprises (MSME) sector. Registered MSMEs have a TIN (Setiawan, 2020). Therefore, it is not surprising that the tax contribution from the final PPh of MSME taxpayers is only around Rp. 7.5 trillion or approximately 1.1% of the total income tax revenue. State revenues from the tax sector long before the outbreak of the Covid-19 pandemic actually tended to be low. One sector that contributes to state tax revenues that should be large but far from the target is the Micro, Small and Medium Enterprises (MSME) sector. Registered MSMEs have a TIN (Setiawan, 2020). Therefore, it is not surprising that the tax contribution from the final PPh of MSME taxpayers is only around Rp. 7.5 trillion or approximately 1.1% of the total income tax revenue. State revenues from the tax sector long before the outbreak of the Covid-19 pandemic actually tended to be low. One sector that contributes to state tax revenues that should be large but far from the target is the Micro, Small and Medium Enterprises (MSME) sector. Registered MSMEs have a TIN (Setiawan, 2020). Therefore, it is not surprising that the tax contribution from the final PPh of MSME taxpayers is only around Rp. 7.5 trillion or approximately 1.1% of the total income tax revenue.